2015
DOI: 10.1111/ajr.12151
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gestational diabetes mellitus: Ethnic disparities

Abstract: The Taiwanese aboriginal women exhibited higher incidence of GDM; thus, we recommend that early screening and health education for pregnant aboriginal women be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Additionally, two were in Vietnam [141, 142], Malaysia [143, 144], Qatar [145, 146], Pakistan [147, 148] and Nepal [149, 150]. One each were from Yemen [151], Hong Kong [152], Singapore [153], Taiwan [154] and Turkmenistan [155].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, two were in Vietnam [141, 142], Malaysia [143, 144], Qatar [145, 146], Pakistan [147, 148] and Nepal [149, 150]. One each were from Yemen [151], Hong Kong [152], Singapore [153], Taiwan [154] and Turkmenistan [155].…”
Section: Resultsmentioning
confidence: 99%
“…A similar report of increased incidence of recurrence of GDM in subsequent pregnancy was found by Ehrlich et al [22] who found that 38% had GDM in subsequent pregnancy compared with 3.5% among women without GDM in first pregnancy. Other studies [12,23] also found previous history of GDM in previous pregnancy as an independent risk factor.…”
Section: Discussionmentioning
confidence: 77%
“…Due to the differences in genetics and diagnostic methods and a lack of universal comprehensive screening during pregnancy, the prevalence of GDM varies widely among countries, ranging from 2-25% [2]. Taiwan does not yet have relevant national statistics, although regional studies have shown a GDM prevalence of approximately 3.5-7.9% [3].…”
Section: Introductionmentioning
confidence: 99%